(untitled) (Journal of Comparative Social Work, 2016)
This paper addresses the enabling and constraining factors that underpin inter-organizational collaboration in Child Welfare and Protection services in Norway and Quebec. Characterized by different regulatory systems, but with a common drive to hierarchically promote cross-agency collaboration, these jurisdictions provide the basis for two instructive and contrasting case studies on the subject. The paper builds on meta-ethnography as a means to synthesize and translate results from separate qualitative research undertakings carried out in each place. It argues that although a core set of properties may be identified as necessary for collaboratives to operate in a successful, sustainable manner; greater attention should be paid to how these properties interact with one another on the ground, given schemes’ particular scope and scale of objectives. Moreover, regulatory provisions aimed at stimulating or mandating cross-agency networks may align with collaborative capacity in various ways, occasionally in a mutually reinforcing, but sometimes antagonistic manner. The conclusions drawn have implications for both research and policy.